Knowledge and practice of infant exposure to sunlight among mothers in the rural villages of Mettu district, southwest Ethiopia - Tadesse, Askalemariam; Yeshanew, Solomon; Gedefa, Abdi Geda (Frontiers in Public Health, 2023)
Background: Sunlight is essential for the synthesis of vitamin D and supports bone growth and strength. The awareness of mothers about the benefit of exposing their infants to sunlight, as well as the practice of doing so, is important to a child's proper growth and development. The current study looked into mothers' knowledge, practice, and factors related to infant sunlight exposure in rural villages in the Mettu district, Southwest Ethiopia.A community-based cross-sectional study design was utilized with randomly selected mothers to newborns from rural areas in the Mettu district. A structured questionnaire was used to collect information. Analysis of the data was performed using the SPSS version 21 software. Both descriptive and inferential analyses were carried out, and p<0.05 was considered statistically significant.Results: Among the 600 mothers who participated in the present study, 397 (66.2%) had good knowledge and 346 (57.7%) practiced proper exposure of their infants to sunlight. Out of the 482 mothers who practiced sunning, 382 (79.3%) did it daily, and 409 (84.8%) began sunning before 45 days of birth. However, 453 (94%) of mothers used lubricants while sunbathing. Sociodemographic characteristics were found to have statistically significant associations with the level of knowledge and practice of mothers. Mothers with four to six children [AOR=0.511, 95% CI: (0.352 -0.741)], and those who got the information from health professionals [AOR=3.285, 95% CI: (2.154, 5.011) for the knowledge level and mothers aged 36 years old and above [AOR=0.801, 95% CI: (0.533, 0.161)]; being married during the data collection period [AOR= 0.370, 95% CI: (0.155, 0.884)], and employed by the government [AOR= 4.081, CI:(1. 477, 11.280)] for the practice level were found to be significantly (p<0.05) associated with the level of infant sunning.Despite the fact that the majority of mothers in the study area had good knowledge and practice of infant sunlight exposure, there are clear signs that further work is needed to narrow the large gap seen in the present findings. Thus, district and zonal health offices, as well as stakeholders working with children, should start periodical maternity health education, and professional development training for health post workers.